2013
DOI: 10.1016/j.jnucmat.2013.01.200
|View full text |Cite
|
Sign up to set email alerts
|

Erosion behavior of actively cooled tungsten under H/He high heat flux load

Abstract: We devised a method to measure erosion in the micrometer range on actively cooled tungsten samples. The method is based on applying micrometer-sized markers onto the side faces of the samples using a focused ion beam. With this method we measured the erosion of tungsten samples exposed to a hydrogen beam with 6% helium content. At 10.5 MW/m² the samples were exposed to particle fluences between 2•10 25 m -2 and 7•10 25 m -2 . Up to 630 pulses with a pulse duration of 30 s were employed. The actively cooled sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…An equilibrium is reached between surface erosion and bubble formation and the thickness of the affected layer is nearly constant above a fluence of 1 Â 10 25 m À2 . We note that the thickness of the affected layer, compared with the 6 at.% He loading, decreases from 400 ± 100 nm to about 250 nm in case of the 1 at.% He loading [9,10] at constant total fluence. Further, we observed the same surface-and bubble layer structures independent of the surface temperature in the investigated temperature range between 1000°C and 2000°C.…”
Section: Surface and Near-surface Modifications Due To Particle Bombamentioning
confidence: 73%
See 1 more Smart Citation
“…An equilibrium is reached between surface erosion and bubble formation and the thickness of the affected layer is nearly constant above a fluence of 1 Â 10 25 m À2 . We note that the thickness of the affected layer, compared with the 6 at.% He loading, decreases from 400 ± 100 nm to about 250 nm in case of the 1 at.% He loading [9,10] at constant total fluence. Further, we observed the same surface-and bubble layer structures independent of the surface temperature in the investigated temperature range between 1000°C and 2000°C.…”
Section: Surface and Near-surface Modifications Due To Particle Bombamentioning
confidence: 73%
“…The applied loading conditions were similar to the previously performed experiments where a particle composition of 94 at.% H and 6 at.% He was used [9,10]. The experiments were performed at 10 ± 0.5 MW/m 2 central heat flux and pulses of 30s duration to ensure the comparability of the results.…”
Section: Loading Conditions In Gladismentioning
confidence: 99%
“…A detailed description of the method and analysis tools as well as the original publication of the erosion data can be found in [13].…”
Section: Methodsmentioning
confidence: 99%
“…Investigations showed that near stoichiometric B 4 C coating can be deposited in high-temperature plasma providing total dissociation of the molecules of initial substance. The conclusion was confirmed experimentally, when B 4 C coating had been successfully deposited in plasma devices (PISCEC-B [5] and tokamak T11-M [6]). The vapor of nontoxic, nonexplosive, and nonhazardous carborane (C 2 B 10 H 12 ) was used as the initial substance for coating deposition in the course of regular discharge in the plasma devices.…”
Section: Introductionmentioning
confidence: 69%